The Influence of Employee Engagement on Turnover Intention Mediated by Job Satisfaction and Quiet Quitting of Generation Z Employee - Parsasi, Wiannisa Rizky; Prawitowati, Tjahjani (SIMAK, 2025)
In a company must have various resources that are useful for the sustainability of a company. One of the resources that is needed in an organisation or company is human resources. This study aims to determine that effect og Quiet Quitting on Turnover Intention and the mediating role of Job Satisfaction and and Quiet Quitting on the effect of job attachment on Turnover Intention. The implications discussed in this study are useful for companies to overcome Quiet Quitting especially for generation Z Employees. The novelty of this research is the study of the Quiet Quitting variable which is a phenomenon in generation Z employees, especially in the post-pandemic period, and there has not been much research on this variable. The author uses a quantitative research design and also uses a software from WarPLS (Partial Least Square). The result of previous research show Employee Engagement has a significant positive effect on Job satisfaction, and Job satisfaction has a significant negative effect on Quiet Quitting and then Quiet Quitting has a significant positive effect on Turnover Intention and Employee Engagement has an effect on Turnover Intentions with satisfaction mediating work and Quiet Quitting.